Odpowiedź :
[tex]x=\frac{2\frac{3}{4} :\frac{1}{7} -22}{6-(-5)} +1\frac{3}{4} =\frac{\frac{11}{4}*7-22 }{6+5} +\frac{7}{4} =\frac{\frac{77}{4} -\frac{88}{4} }{11} +\frac{7}{4} =\frac{\frac{-11}{4} }{11} +\frac{7}{4} =\frac{-11}{4} *\frac{1}{11} +\frac{7}{4} =\frac{-1}{4} +\frac{7}{4} =\frac{6}{4} =\frac{3}{2} =1\frac{1}{2}[/tex]
[tex]z=2-\frac{8-\frac{1}{2} }{12+\frac{1}{2} } =2-\frac{\frac{16}{2} -\frac{1}{2} }{\frac{24}{2} +\frac{1}{2} } =2-\frac{\frac{15}{2} }{\frac{25}{2} } =2-\frac{15}{2} *\frac{2}{25} =2-\frac{3}{5} =\frac{10}{5} -\frac{3}{5} =\frac{7}{5}[/tex]
[tex]y=\frac{\frac{6}{11} -\frac{15}{45} }{\frac{11}{3}-2\frac{1}{2} } *2\frac{3}{4} =\frac{\frac{6}{11} -\frac{1}{3} }{\frac{11}{3} -\frac{5}{2} } *\frac{11}{4} =\frac{\frac{18}{33}-\frac{11}{33} }{\frac{22}{6} -\frac{15}{6} } *\frac{11}{4} =\frac{\frac{7}{33}}{\frac{7}{6} } *\frac{11}{4} =\frac{7}{33} *\frac{6}{7} *\frac{11}{4} =\frac{6}{33} *\frac{11}{4} =\frac{2}{11} *\frac{11}{4} =\frac{1}{2}[/tex]